Targeting Natural Killer cells to Acute Myeloid Leukemia in vitro with a CD16x33 bispecific killer cell engager (BiKE) and ADAM17 inhibition - Wiernik, Andres (2013)
PURPOSE: The graft versus leukemia (GVL) effect by Natural Killer (NK) cells prevents relapse following hematopoietic stem cell transplantation. We determined whether a novel bi-specific killer cell engager (BiKE) signaling through CD16 and targeting CD33 could activate NK cells at high potency against AML targets. EXPERIMENTAL DESIGN: We investigated the ability of our fully humanized CD16x33 BiKE to trigger in vitro NK cell activation against HL60 (CD33(+)), RAJI (CD33(−)), and primary AML targets (de novo, refractory and post transplant) to determine whether treatment with CD16x33 BiKE in combination with an ADAM17 inhibitor could prevent CD16 shedding (a novel inhibitory mechanism induced by NK cell activation) and overcome inhibition of class I MHC recognizing inhibitory receptors. RESULTS: NK cell cytotoxicity and cytokine release were specifically triggered by the CD16x33 BiKE when cells were cultured with HL60 targets, CD33(+) de novo and refractory AML targets. Combination treatment with CD16x33 BiKE and ADAM17 inhibitor resulted in inhibition of CD16 shedding in NK cells, and enhanced NK cell activation. Treatment of NK cells from double umbilical cord blood transplant (UCBT) recipients with the CD16x33 BiKE resulted in activation, especially in those recipients with CMV reactivation. CONCLUSION: CD16x33 BiKE can overcome self inhibitory signals and effectively elicit NK cell effector activity against AML. These in vitro studies highlight the potential of CD16x33 BiKE ± ADAM17 inhibition to enhance NK cell activation and specificity against CD33(+) AML, which optimally could be applied in patients with relapsed AML or for adjuvant anti-leukemic therapy post-transplantation.